A High-Throughput Method to Analyze the Interaction Proteins With p22 Protein of African Swine Fever Virus In Vitro - Zhu, Xuejiao; Fan, Baochao; Zhou, Junming; Wang, Dandan; Fan, Huiying; Li, Bin (Frontiers in Veterinary Science, 2021)
African Swine Fever Virus (ASFV) has been identified as the agent of ASF, resulting in a mortality rate of nearly 100% in domestic pigs worldwide. Protein p22 encoded by gene KP177R has been reported to be localized at the inner envelope of the virus, while the function of p22 remains unclear. In this study, p22 interacted proteins of the host were identified by a high throughput method and analyzed by Go terms and KEGG pathways, numerous cellular proteins in 293-T that interacted with p22 protein were identified. These interacted proteins were related to the biological processes of binding, cell structure, signal transduction, cell adhesion, etc. At the same time, the interacted proteins participated in several KEGG pathways like ribosome, splicesome, etc. The key proteins in PPI network were closely related to actin filament organization and movement, resulting in affecting the process of phagocytosis and endocytosis. A large number of proteins interacted with p22 were identified, providing a large database which should be very useful to elucidate the function of p22 in the near future, laying the foundation for elucidating the mechanism of ASFV.